Utility of Rice Bran Mixed with Fermentation Extract of Vegetable Waste Unconditioned as Probiotics from Vegetable Market - Cahya Setya Utama; Nyoman Suthama; Bambang Sulistiyanto; Bhakti Etza Setiani (Chemical Engineering Diponegoro University, 2013)
The aimed of the study was to enhance utilization of Lactobacillus Sp. and Saccharomyces sp. as starter for fermentation of waste cabbage and green mustard to enhance the utility of rice bran as an ingredient of poultry feed. The first stage of the study was to characterize the extract of fermented wasted vegetable with difference concentration of glucose and different period of time for incubation. Completely randomized design using 3 x 3 factorial with three replications was used for the first stage of the study. The second stage of the study was to evaluate the effectiveness of the extract of fermented wasted vegetable to improve the quality and utility of rice bran. Completely randomized design with four treatments and 4 replications. The third stage of the study was to obtain the value of nitrogen, calcium and phosphorus retention, as well as metabolic energy of rice bran after fermentation in broiler hatching. The third stage analysis was conducted by t-test analysis. The results of the study showed that the microbial characteristics on the extract of fermented wasted vegetable in two days incubation time and 2% concentration of glucose was able to produce pH of 3.80, log of total lactic acid bacteria 7.38 and types of microbes that grow predominantly were Lactobacillus Sp. and Saccharomyces Sp. The effectiveness of the extract fermented wasted vegetable for the fermentation of rice bran were shown in additional concentration of extract wasted vegetable of 40% with a moisture content of toluene 65.24%, 13.36% ash, 14.93% protein, 7.61% crude fat, 12.39% crude fiber, nitrogen free extract material (NFE) 51.59% and 0.07% biomass. The biological value and the availability of fermented rice bran were higher than unfermented rice bran on the broiler chickens after hatching. The values were justified from nitrogen, calcium and phosphorus retention also metabolic energy. The study concluded that the benefits and utility of rice bran could increased by fermentation using 40% extract of fermented wasted vegetable from vegetable market with 2% glucose concentration and 2 days incubation time.Doi: 10.12777/ijse.4.2.2013.97-102 [How to cite this article: Utama, C.S., Suthama, N., Sulistiyanto, B., Setiani, B.E. (2013). Utility of Rice Bran Mixed with Fermentation Extract of Vegetable Waste Unconditioned as Probiotics from Vegetable Market. International Journal of Science and Engineering, 4(2),97-101. Doi: 10.12777/ijse.4.2.2013.97-102]